THE IMPACT OF INNOVATIVE FOOD SUPPLEMENTS BASED ON PHLOMOIDES NUDA ON HUMAN HEALTH - I.I. Ibrohimova, M.M.Mexmonxonov, D.R. Haydarova (Research Focus International Scientific Journal, 2025)
In modern medicine, food supplements created from ecological and natural medicinal plants play a significant role in enhancing health. Phlomoides nuda, with its high content of macro- and microelements, as well as biologically active compounds, can have beneficial effects on the human body. This article analyzes the health effects and innovative potential of food supplements based on the composition of Phlomoides nuda collected during its flowering period.